Mutual recognition: Promise and denial, from Sapiens to Brexit - Nicolaidis, K (Oxford University Press, 2017)
This contribution argues that the European crisis in general and Brexit in particular, can be seen to reflect the partial loss of the ethos of a principle that has been at the heart of the EU, namely mutual recognition. While familiar to legal scholars as a norm governing the integration of markets and the management of conflicts of law, the essay seeks to show how this principle bears on our current European predicament as a philosophical concept and a form of governance between states before dwelling on the intricacies of mutual recognition in the EU single market. Because recognition is sought, obtained or denied in all social spheres, every discipline has its own complex variation on this simple theme requiring to connect legal theory with anthropology, philosophy, history, sociology and international relations. The essay spans all these fields through eight takes (mutual Recognition shunned, invented, enshrined, constitutionalised, managed, ‘on trial’, lost, and for grabs) which can also be interpreted as different time horizons (from Sapiens to Brexit through Westphalia). Each take provides a variation on what is referred to as “mutual recognition paradox”, eg how to increase mutual engagement and mutual deference at the very same time.